2017
DOI: 10.1001/jamaoncol.2016.6762
|View full text |Cite|
|
Sign up to set email alerts
|

Mismatch Repair Deficiency, Microsatellite Instability, and Survival

Abstract: In the MAGIC trial, MMRD and high MSI were associated with a positive prognostic effect in patients treated with surgery alone and a differentially negative prognostic effect in patients treated with chemotherapy. If independently validated, MSI or MMRD determined by preoperative biopsies could be used to select patients for perioperative chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
245
4
27

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 433 publications
(295 citation statements)
references
References 35 publications
19
245
4
27
Order By: Relevance
“…Here we showed that MSI is associated with specific clinical and pathological features of GC [3-5], even if the lack of association with N0 disease in this series may be related to the enrollment of patients with poorer disease stage. In multivariable analysis, a nonsignificant trend for better DFS and OS in MSI-high Asian GC patients was still evident following adjuvant chemo(radio)therapy treatment, even if the small number of patients with MSI-high status may have halted the formal achievement of a statistically significant result.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Here we showed that MSI is associated with specific clinical and pathological features of GC [3-5], even if the lack of association with N0 disease in this series may be related to the enrollment of patients with poorer disease stage. In multivariable analysis, a nonsignificant trend for better DFS and OS in MSI-high Asian GC patients was still evident following adjuvant chemo(radio)therapy treatment, even if the small number of patients with MSI-high status may have halted the formal achievement of a statistically significant result.…”
Section: Discussionmentioning
confidence: 86%
“…However, the clinical translation of MSI as a prognostic biomarker for GC patients has been hampered by the retrospective and heterogeneous nature of available series, the relatively low frequency of MSI-high status, and the potential detrimental effect of “over-treatments” with perioperative chemotherapy in MSI-high GC patients. The post hoc analysis of the MAGIC trial [5] showed that MSI-high status is a good prognostic factor in GC patients treated with surgery alone, whereas it may be a negative predictive marker in patients randomized to perioperative combination chemotherapy. However, it must be pointed out that disease outcomes and treatment efficacy are markedly different in Western versus Eastern countries and, consequently, there may be a possible differential prognostic or even predictive role of MSI-high status that still remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In February 2017, an exploratory post hoc analysis from the MAGIC trial was published [12]. The goal was to evaluate the proportion of patients with high MSI (MSI-H) or mismatch repair deficiency (MMRD) in the 2 cohorts, and if these biomarkers had prognostic effect on survival.…”
Section: Discussionmentioning
confidence: 99%
“…Při-pravovaná studie EORTC 1707 plánuje srovnat efekt pooperační chemoterapie s kombinací nivolumab + ipilimumab u prognosticky nepříznivé skupiny pa cientů, která operací po neoadjuvanci dosáhla pouze R1 resekce, nebo s N+ stavem po operaci. Post-hoc analýza studie MAGIC [21] stejné skupiny autorů provedla rozbor v souvislosti s MSI/ dMMR stavem. Pa cienti, kteří mají nádory s MSI--high (tato skupina představovala ve zmiňované studii okolo 10 % pa cientů), mají lepší prognózu a neprofitují z chemoterapie, naopak analogicky pa cienti, kteří nemají MSI-high nebo dMMR, měli benefit z aplikované chemoterapie.…”
Section: Checkpoint Inhibitory U Potenciálně Operabilního Karcinomu žunclassified